The Oxford handbook of energy and society - Davidson, Debra J. ca. 20./21. Jh; Groß, Matthias 1969- (Oxford University Press, 2018)
"This volume offers a collection of contemporary sociological research on energy-society relations, highlighting the growing instability and disruptions associated with fossil-fuel-dependence, and the emerging challenges and innovations associated with a transition away from fossil fuels. Regional case studies of different energy resources from around the world are featured, as are the roles of politics, markets, technology, social movements, and consumers, all contributing to a complex systems perspective on the uncertain future of energy-society relations" ...
Includes bibliographical references
Keywords: Energy policy; Energy consumption; Energy security; Environmental responsibility; Power resources; Renewable energy sources; Energiewende; Energie; Gesellschaft; Energieverbrauch